2017
DOI: 10.1016/j.jcs.2017.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide association studies (GWAS) of element contents in grain with a special focus on zinc and iron in a world collection of barley (Hordeum vulgare L.)

Abstract: Genome wide association studies (GWAS) were carried out to map Quantitative Trait Loci (QTL) associated with element contents in the grain using 336 spring barley. Of the elements analyzed, Fe content ranged from 21.9 to 91.0 mg kg À1 , Zn from 10.4 to 54.5 mg kg À1 , Ba from 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…The analyses of the tested populations helped to identify specific QTL for each of the studied indicators and map them on chromosomes. The QTL identified are valuable for the future development of barley cultivars with increased content of nutrients, especially Zn and Fe [35].…”
Section: Fe Mn Znmentioning
confidence: 99%
“…The analyses of the tested populations helped to identify specific QTL for each of the studied indicators and map them on chromosomes. The QTL identified are valuable for the future development of barley cultivars with increased content of nutrients, especially Zn and Fe [35].…”
Section: Fe Mn Znmentioning
confidence: 99%
“…In other studies, diverse barley lines from different regions, including the US (Zhou and Steffenson, 2013 ; Genievskaya et al, 2018 ), Europe (Xu et al, 2018 ), and India (Visioni et al, 2018 ), were used to identify the genetic architecture of complex traits (heading time, number of kernels per spike, grain yield) and disease resistance (durable spot, stripe rust) in barley. Although some studies used worldwide collections of barley germplasm, few have included barley varieties from Tibet (Pasam et al, 2012 ; Gyawali et al, 2017 ). Over the past decade, studies in barley (Cuesta-Marcos et al, 2008 ), wheat (Kiseleva et al, 2016 ), and rice (Yan et al, 2011 ) have shown that variations in heading date (HD), plant height (PH), and spike length (SL) contribute to environmental adaptation in cereal crops and also influence grain yield.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 14 QTLs for Fe and Zn as well as high-priority candidate genes were identified such as OsYSL1 and OsMTP1 for Fe and OsARD2, OsIRT1, OsNAS1 , and OsNAS2 for Zn in rice seeds ( Anuradha et al, 2012 ). GWAS approach has also been used to identify major loci for different elemental concentrations such as Ca, Fe, and Zn in wheat ( Velu et al, 2016 ; Alomari et al, 2017 ), Fe and Zn in barley ( Mamo et al, 2014 ; Gyawali et al, 2017 ), and Fe and Zn in maize ( Hindu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%